Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.7150/ijms.51382
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human amylin aggregation by Flavonoid Chrysin: An in-silico and in-vitro approach

Abstract: Islet amyloid polypeptide (amylin), consecrated by the pancreatic β-cells with insulin, has a significant role to play in maintaining homeostasis of islet cell hormones. Alzheimer's disease is the predominant source of dementia. However, its etiology remains uncertain; it appears that type 2 diabetes mellitus and other prediabetic states of insulin resistance contribute to the intermittent Alzheimer's disease presence. Amylin is abnormally elevated in Type II diabetes patients, accumulated into amylin aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…Additionally, according to the present study’s findings, the potential clinical implications of these binding interactions in the context of consumption and metabolic health of many additives, such as sweeteners, could be predicted and ensured by both in vitro and in vivo studies. Based on the literature and in agreement with the above results, many natural and synthetic compounds showed a potential inhibition effect against many hormones and enzymes during consumption, such as amylin, , FSH and LH, COX I/II, prostaglandin E2, and antioxidant enzymes . The current study’s findings open the perspectives toward using in silico techniques to predict the negative implications of many food additives, including sweeteners.…”
Section: Results and Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Additionally, according to the present study’s findings, the potential clinical implications of these binding interactions in the context of consumption and metabolic health of many additives, such as sweeteners, could be predicted and ensured by both in vitro and in vivo studies. Based on the literature and in agreement with the above results, many natural and synthetic compounds showed a potential inhibition effect against many hormones and enzymes during consumption, such as amylin, , FSH and LH, COX I/II, prostaglandin E2, and antioxidant enzymes . The current study’s findings open the perspectives toward using in silico techniques to predict the negative implications of many food additives, including sweeteners.…”
Section: Results and Discussionsupporting
confidence: 85%
“…For example, the flavonoid chrysin inhibited amylin through in silico and in vitro approaches, with a binding free energy of −6.45 kcal/mol. 88 Also, Fang et al 89 revealed amylin inhibition using epigallocatechin-3-gallate (−4.28 kcal/mol) and genistein (−5.10 kcal/mol). In the present study, the docking study with amylin (PDB ID: 2L86 ), aspartame (−5.8 kcal/mol), sucralose (−5.5 kcal/mol), and sucrose (−5.4 kcal/mol) showed comparable results to the literature ( Figure 2 ), which may the cause for the lower concentrations of amylin as shown in Table 3 .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, autophagy activation has protective effects and inhibits pancreatic β cell death, being a natural defense ( 42 , 43 ). Flavonoids have also been involved in the protection of the deleterious effects of hIAPP aggregates in these cells ( 105 109 ). Apart from the actions of flavonoids already explained, flavonoids have been also involved in an increase in antioxidant enzymes, as a protective mechanism ( 110 , 111 ).…”
Section: Prevention Of Beta Cell Dysfunction By Polyphenolsmentioning
confidence: 99%
“…Coumarins due to their aromatic structures, are known to potently inhibit cholinesterases (acetylcholinesterase, and butyrylcholinesterase) enzymes that promote and propagate β -amyloid aggregation (37), and also Monamine Oxidase (MAO) which induces β -amyloid deposition (38) (39). Various avonoids inhibit human amylin amyloidosis through unknown mechanism (40).…”
Section: Introductionmentioning
confidence: 99%